A Validated RP-HPLC Method for the Determination of Recombinant Human Insulin in Bulk and Pharmaceutical Dosage Form - B. A. Moussa; F. Farouk; H. M. E. Azzazy (E-Journal of Chemistry)
A modified RP-HPLC method was developed for the quantitative determination of recombinant human insulin in bulk and pharmaceutical dosage form with reduced retention time. Study of the effects of the column temperature, pH of the mobile phase and presence of vial additives (phenol and m-cresol), or impurities (A-21 Disamido) on the accuracy of the assay were assessed. Separation was achieved using a Hypersil BDS C-18 column and the mobile phase was composed of solution A (aqueous solution of 28.3 anhydrous Na2SO4g/L, pH 2.3) and solution B (28.5 g anhydrous Na2SO4 g/L in 50:50 mixture of water and acetonitrile, pH 2.3) in a ratio 48:52 (v/v) at 45–50 °C. The column temperature was 40 °C, the flow rate was 1 mL/min and detection was performed at 216 nm. The procedures were validated according to international conference on harmonization (ICH) guidelines. Recovery study was done applying standard addition technique for further validation of the procedure. The retention time of recombinant human insulin was 19.7 min as compared to 29 min obtained by the reference method. Analytical conditions fluctuations or presence of vial additives or impurities did not show any significant effect on the accuracy of the method. The prepared standard insulin solution in 0.01 N HCl was found to be stable for 5 days. Statistical comparison showed no significant difference between the described method and reference method regarding the accuracy and precision. The modified method can be applied for routine quality control applications for determination of recombinant human insulin.